An Introduction to Machine Learning Games and Its Application for Kids in Fun Project - Fahrudin, Tresna Maulana (IJCONSIST JOURNALS, 2020)
Industrial Revolution 4.0 is the right time to democratize artificial intelligence in the world. It can be started from education, the target is the level of elementary, middle and high school. But the general curriculum still around in natural science, social science and language science. The challenge is how to introduce artificial intelligence earlier to the student and how to combine its material with the curriculum. “Machine Learning for Kids” is a web-based application which kids can explore artificial intelligence, especially in machine learning field with a fun project. The application provided to create a new project like animal classification. Kids can add a new label, such as mammal, insect, amphibian, bird, fish and etc. They have to add the animal name as an example of training data into each label. After kids added the training data, they can create the machine learning model. The experiment showed the confidence of the machine learning model test with a member of example reached 100%, the label prediction of all example was accurate. While the confidence of machine learning model test with another member of example reached between 14-17%, the label prediction of all example was also accurate. We recommended “Machine Learning for Kids” is one of the best web-based application for kids to explorer machine learning easily.